The role of EZH2-VAV interaction in tumorigenesis - Wong, Jong Fu (2015)
Polycomb group protein EZH2 is a histone methyltransferase that modifies chromatin structure to alter gene expression during various important biological and pathogenic processes. We have previously identified a novel cytosolic role for EZH2 in the regulation of cell signaling via interaction with VAV family proteins; whether EZH2 interactions with the VAV are critical for tumorigenesis has not been explored. Here, we report that EZH2 interactions with VAV critically regulate cell adhesion, promote cellular transformation, tumor growth and metastasis through talin1 methylation. While cytosolic EZH2 shows greater transforming and metastatic capacity than wild-type EZH2, targeted disruption of EZH2-VAV interaction abolishes EZH2-promoted tumorigenesis. EZH2-mediated talin1 methylation enhances talin1 cleavage and thereby promotes turnover of adhesion structures and likely directly contributes to tumorigenesis. Our data provides a novel mechanistic insight into the cellular transformation associated with EZH2 overexpression. This may be a critical step in the initiation of cellular transformation preceding the well-established function of EZH2 in epigenetic silencing of tumor suppressors. Hence, the interference of EZH2-VAV interaction could be an alternative intervention strategy for treatment of cancers associated with EZH2 overexpression.